Bis(μ-l-arginine-κ3N2,O:O′)bis(l-arginine-κ2N2,O)tetra-μ-chlorido-tetrachloridotetracopper(II) - P. Arularasan; B.Sivakumar; G. Chakkaravarthi; R. Mohan (Acta Crystallographica Section E, 2013)
The title compound, [Cu4Cl8(C6H14N4O2)4], contains four molecules in the asymmetric unit. In the molecular structure, each of the four Cu2+ ions binds to three Cl atoms, one N atom and one O atom, resulting in distorted square-pyramidal coordination environments. The molecular structure is stabilized by weak C—H...O and N—H...Cl hydrogen bonds. The crystal structure exhibit weak intermolecular N—H...O, C—H...O and N—H...Cl interactions, generating a three-dimensional network.